Case of cytomegalovirus retinitis aggravated by sub-Tenon injection of triamcinolone acetonide with subsequent metastatic liver cancer - Yamamoto Y; Kato Y; Tabuchi H; Fukushima A (Clinical Ophthalmology, 2013)
Yumiko Yamamoto,1 Yoshitake Kato,2 Hitoshi Tabuchi,2 Atsuki Fukushima11Department of Ophthalmology and Visual Science, Kochi Medical School, Kochi, Japan; 2Department of Ophthalmology, Tsukazaki Hospital, Hyogo, JapanAbstract: We report a case of cytomegalovirus (CMV) retinitis in an immunocompetent patient who was resistant to antiviral treatment, and in whom fatal metastatic liver cancer was later detected. A 74-year-old Japanese man visited our ophthalmology clinic in May 2011. He had a history of well controlled type 2 diabetes and colon cancer, and underwent successful surgical treatment in 2008. In April 2011, he was diagnosed with uveitis affecting his left eye and received posterior sub-Tenon injection of triamcinolone acetonide. He was referred to us because of aggravation of the retinal lesion. Funduscopic examination of the left eye revealed arcuate, whitish, necrotizing retinitis with hemorrhage along the temporal arcade of the retina. Polymerase chain reaction of the aqueous fluid was positive for CMV DNA. Because of diagnosis of CMV retinitis in his left eye, he was referred to an internist and investigated for systemic CMV infection or any serious disease which could cause immunocompromise, but neither was detected. Despite an intensive course of intravitreous ganciclovir and oral valganciclovir, the retinitis did not resolve. In June 2012, 14 months after the initial ocular symptoms, metastatic liver cancer was found and the patient passed away. When CMV retinitis is resistant to antiviral treatment or recurs in an immunocompetent patient, it is important that ophthalmologists undertake systemic investigation for occult malignancy.Keywords: cytomegalovirus, retinitis, uveitis, immunocompromised, immunocompetent, triamcinolone acetonide, diabetes, ganciclovir, valganciclovir